An Educational Intervention Using Health Belief Model on Smoking Preventive Behavior among Female Teenagers - Zahra Rahnavard; Masooma Mohammadi; Fatemeh Rajabi; Mitra Zolfaghari (Tehran University of Medical Sciences, 2011)
Background & Aim: Cigarette smoking is a common risky behavior among teenagers. Theories and models of health education aim to design effective educational programs. This study has been conducted to assess the effect of a health education program designed based on the health belief model on preventive smoking behaviors among female teenagers. Methods & Materials: In this quasi-experimental study, 176 female teenagers from the Educational Cultural Centers of 17 zones of Tehran Municipality were randomly allocated to two equal experiment and control groups (88 girls in each group). The designed educational program was presented to the experiment group through three lecture and question/answer 45 minute sessions. Data were collected using a questionnaire before and eight weeks after the intervention. Data were analyzed using the SPSS-16. Results: There was no significant difference between the two groups in the characteristics of the participants before the intervention. Comparison of the two experiment and control groups after education showed that the mean score of all studied constructs of the health belief model (i.e., susceptibility, severity, benefits and barriers, cues to action), as well as the preventive behaviors were increased significantly. Conclusion: The results of this study showed that the program seems to be helpful in promoting the smoking preventive behavior among teenagers.